Development of Inquiry-Based Solar System Augmented Reality Science Learning Media - Yonatan Vari; Sarwanto; Sri Yamtinah (Postgraduate, University of Mataram, 2023)
Science learning in the 21st Century needs to adapt to technological developments in the Era of Revolution 4.0. 21st Century science learning uses digital technology, namely Augmented Reality combined with an inquiry learning model on the Solar System material. The research aims to determine the feasibility of the Inquiry-based Solar System Augmented Reality (SSAR) Learning Media being developed. Inquiry-based SSAR Learning Media Research is development research that uses the ADDIE Development Model with assessment by 8 validators using a 1-5 Likert scale. Inquiry-based SSAR learning media which was developed through the Analysis, Design and Development stages. The Analysis stage is carried out through an initial preliminary study to determine needs analysis. The results of the needs analysis are used in the design stage and then realized in the Development stage. The Media Development stage carried out a feasibility test through validation by 8 experts. The feasibility of SSAR Learning Media is reviewed including Media, Material, Learning and linguistic aspects. The results of the assessment by the Validator were analyzed using the Aiken formula with validation criteria > 0.75. Inquiry-based SSAR Learning Media indicators based on Aiken Validation analysis obtained validation results with a score of 0.85 > 0.75 indicating that Inquiry-based SSAR Learning Media is suitable for use in the science learning process on Solar System material